OPTIMIZATION OF WAREHOUSE BALANCE MONITORING WITH GOLEK (GUDANG ONLINE LEK) - Ibnu Gunawan; Zulfahmi Syahputra; Muhammad Syahputra Novelan (INFOKUM, 2022)
The warehouse is a place for receiving, temporarily storing and stocking parts, materials, and goods to be used for production needs or production support. To control the material stock balance, it is necessary to monitor the material balance data in accordance with the actual material balance, so that there is no discrepancy between data deviation and actual balance, which can lead to interruption of the production process due to unavailability of material or errors in material stock planning. Material procurement in Pangkalan Susu steam power plant is usually divided into 2 areas, namely material inventory, which is usually recorded in the application maximo. The operating budget or code GL is normally used for this material. Meanwhile, the material expense is the material that is procured to anticipate the overhaul needs, which is used at the same time and cannot be stored in the warehouse. The capital budget is usually used for these materials. Until now, stock monitoring can only monitor the material stock through TUKG7, while the material cost cannot be monitored, so there is a deviation between the actual stock and the TUKG7 stock, resulting in an interruption of the production process due to unavailable materials and errors in material procurement. For this reason, a stock monitoring application (GOLEK) has been developed that allows real-time monitoring whenever and wherever it is.